PERAN ORGANISASI REMAS DALAM MENINGKATKAN PARTISIPASI KEGIATAN KEAGAMAAN Di MASYARAKAT: Study di masjid An-nur Kecamatan wlingi - Okta Dwi Rismaningsih; Hery Suprayitno; Bina Andari (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2018)
This research reveals about strategy of adolescent of mosque in forming adolescent character in sub district of Babadan Sub Wlingi Blitar Regency through activities of Teens of Mosque The purpose of this research is to describe strategy of youth of mosque in forming adolescent character in sub district Babadan Sub Wlingi Kabupaen Blitar And also obstacles. The theory used in this research is adaptive strategy theory and observational social learning theory. This study uses a qualitative method. Information in this research is the board and members of the Youth Mosque. Observation techniques, interviews, and documentation is to collect data. The strategies used in the formation of religious characters through religious habituation by conducting routine religious activities is the result of research. Through habituation such as work of devotion and helping the needy citizen is forming character of adolescent strategy toward social awareness. In the formation of teenage characters mosque has a strategy through habituation greet each other and create a conducive atmosphere. The obstacles encountered are the lack of interest of adolescents to follow every activity of Teens Mosque so that needed motivation and more interesting activity again in increasing participation of social activities in society.